positive electrode active material

CN122930896APending Publication Date: 2026-10-16TOYOTA JIDOSHA KK
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202610374235.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2025-04-02
Filing Date
2026-03-25
Publication Date
2026-10-16

AI Technical Summary

Benefits of technology

[0025] According to this disclosure, a positive electrode active material capable of reducing the resistance of a battery can be provided.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122930896A_ABST
    Figure CN122930896A_ABST
Patent Text Reader

Abstract

A positive electrode active material containing at least one element selected from the group consisting of Ni element, Co element, and Mn element, the positive electrode active material having a shape in which two or more primary particles are stacked, the primary particles being single crystals having a crystal structure belonging to space group R-3m, each of the primary particles being oriented and stacked in such a manner that a 003 plane of each of the primary particles is parallel, and in a direction parallel to the 003 plane of each of the primary particles, a ratio of a length of a shortest primary particle to a length of a longest primary particle among a plurality of the primary particles is 0.95 to 1.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This disclosure relates to positive electrode active materials. Background Technology

[0002] Various technologies have been proposed regarding the positive electrode active material disclosed in Japanese Patent Application Publication No. 2013-65397. Summary of the Invention

[0003] In the past, various positive electrode active materials have been proposed in order to obtain positive electrodes with high battery characteristics such as high cycle performance and high output performance.

[0004] Japanese Patent Application Publication No. 2013-65397 describes a cathode active material where the primary particles have a short-axis plane of 003, and secondary particles are formed by bonding together through these short-axis planes. It is argued that due to the uneven length of the short-axis planes, the material has a high specific surface area, resulting in higher battery resistance.

[0005] This disclosure was made in view of the above-mentioned circumstances, and its main purpose is to provide a positive electrode active material that can reduce the resistance of a battery.

[0006] That is, this disclosure includes the following methods.

[0007] <1>

[0008] A positive electrode active material, wherein the positive electrode active material contains at least one element selected from Ni, Co, and Mn.

[0009] The positive electrode active material has a shape formed by the stacking of two or more primary particles.

[0010] The primary particles are single crystals with a crystal structure belonging to space group R-3m, and the primary particles are stacked with their 003 planes parallel.

[0011] In a direction parallel to the 003 plane of each of the primary particles, the ratio of the length of the shortest primary particle to the length of the longest primary particle is 0.95 to 1.

[0012] <2>

[0013] According to <1>, the positive electrode active material has a shape of stacking two or more but less than ten primary particles, each of the primary particles does not stack in a direction parallel to the 003 plane of each primary particle, and the short side direction of the positive electrode active material is parallel to the 003 plane of each primary particle.

[0014] <3>

[0015] According to <1> or <2>, the positive electrode active material, when viewed in cross-section using a transmission electron microscope, exposes the 003 surface originating from the primary particle in a direction parallel to the 003 surface of each primary particle, and exposes other surfaces other than the 003 surface of each primary particle in a direction perpendicular to the 003 surface of each primary particle, wherein the other surfaces other than the 003 surface of each primary particle are the 012 surface, 101 surface, 104 surface, or 110 surface.

[0016] <4>

[0017] A battery comprising <1> ~ <3> The positive electrode layer of the positive electrode active material as described in any one of the above.

[0018] <5>

[0019] <1> ~ <3> The method for manufacturing the positive electrode active material according to any one of the following methods comprises:

[0020] In the first stage of the firing process, a first mixture of transition metal hydroxide and lithium compound is fired at 700°C to 1100°C to obtain the precursor of the positive electrode active material.

[0021] The magnetic field application process involves applying a magnetic field to a slurry formed by dispersing the precursor of the positive electrode active material in a solvent.

[0022] The drying process dries the slurry to obtain a dried product.

[0023] The second-stage firing process involves firing the dried material at 800℃~1000℃ to obtain the second-stage fired product; and

[0024] In the cooling process, the second-stage fired material is cooled at a cooling rate of 0.2℃ / min to 0.5℃ / min to obtain the positive electrode active material.

[0025] According to this disclosure, a positive electrode active material capable of reducing the resistance of a battery can be provided. Attached Figure Description

[0026] The features, advantages, and technical and industrial significance of exemplary embodiments of the present invention will now be described in conjunction with the accompanying drawings, wherein the same symbols denote the same elements.

[0027] Figure 1 This is a schematic diagram illustrating an example of the structure of the positive electrode active material of this disclosure. Detailed Implementation

[0028] In this disclosure, an example of a method for calculating the average particle size is described below. First, for a given particle, the particle size is calculated by considering it as spherical in a transmission electron microscope (TEM) image or a scanning electron microscope (SEM) image at an appropriate magnification (e.g., 50,000 to 1,000,000 times). This particle size calculation based on TEM or SEM observations is performed on 2 to 300 particles of the same type, and the average value of these particles is taken as the average particle size.

[0029] 1. Positive electrode active material

[0030] In this disclosure, a positive electrode active material is provided, the positive electrode active material containing at least one element selected from Ni, Co and Mn, the positive electrode active material having a shape formed by stacking two or more primary particles, the primary particles being single crystals having a crystal structure belonging to space group R-3m, each of the primary particles being stacked in an orientation parallel to the 003 plane of each primary particle, and in a direction parallel to the 003 plane of each primary particle, the ratio of the length of the shortest primary particle to the length of the longest primary particle is 0.95 to 1.

[0031] In this disclosure, by bonding the 003 surfaces, which serve as the stabilizing surfaces of the primary particles, to each other, the specific surface area is reduced, thereby suppressing the battery resistance. Furthermore, by preventing the stacking of primary particles from shifting, the fill rate can be increased, thus improving the battery capacity.

[0032] Figure 1 This is a schematic diagram illustrating an example of the structure of the positive electrode active material of this disclosure. For example... Figure 1 As shown, the positive electrode active material 100 of this disclosure has a first particle 10, a second particle 20, a third particle 30 and a fourth particle 40 connected in sequence.

[0033] Each of the primary particles 10 to 40 is stacked with its orientation parallel to the 003 plane of each of the primary particles 10 to 40. That is, the primary particles 10 to 40 are not stacked in the direction parallel to the 003 plane.

[0034] In the cross-sectional view of the positive electrode active material 100, the length L of each primary particle 10-40 is equal in the direction parallel to the 003 plane of each primary particle 10-40.

[0035] When the positive electrode active material 100 is cross-sectioned, the 003 surfaces of the primary particles 10 and 40 at both ends of the stacking direction Z are exposed at the outer edge, and the other surfaces of the primary particles 10 to 40, namely the 104 surfaces, are exposed on the surface in the direction perpendicular to the 003 surfaces of each primary particle 10 to 40.

[0036] When the positive electrode active material 100 is viewed in cross section, the short side direction X of the positive electrode active material 100 is parallel to the 003 plane of each primary particle 10~40.

[0037] The positive electrode active material only needs to contain at least one transition metal (TM) element selected from Ni, Co, and Mn. The positive electrode active material can be a lithium transition metal composite oxide containing Li, a transition metal, and O. The lithium transition metal composite oxide only needs to contain at least Ni as a transition metal; it can contain two, three, or even four or more transition metals. Examples of transition metals include Ti, V, Cr, Mn, Fe, Co, Ni, Zr, and Nb.

[0038] Lithium transition metal composite oxides only need to contain at least Ni as a transition metal, and may further contain, for example, Co and Mn as transition metals.

[0039] Lithium transition metal composite oxides may contain metals other than Li and transition metals, such as M. 1 (Including semi-metals). As other metals M 1 Examples include Al, Si, Ga, Ge, In, and Sn.

[0040] Lithium transition metal composite oxides can contain Li, Ni, Co, Mn, and O.

[0041] Compared to the total of 1 mol of all metals other than Li contained in the lithium transition metal composite oxide, the total proportion of Ni, Co, and Mn contained in the lithium transition metal composite oxide is, for example, 0.80 mol or more, 0.90 mol or more, 0.95 mol or more, or 1 mol. It should be noted that "total of Ni, Co, and Mn" also includes the case where the proportion of one or two of Ni, Co, and Mn is 0.

[0042] Lithium transition metal composite oxides can have the following composition: Li x Ni a Co b Mn c O yThe composition represented by (0.1≤x≤1.5, 0.5≤a≤1.0, 0≤b≤0.3, 0≤c≤0.3, a+b+c=1.0, 1.5≤y≤2.1).

[0043] In the general formula, the Li composition ratio "x" only needs to satisfy the relationship "0.1≤x≤1.5". For example, the Li composition ratio "x" can be 0.4 or higher, 0.6 or higher, 0.8 or higher, 1.0 or higher, or 1.1 or higher. For example, the Li composition ratio "x" can be 1.4 or lower or 1.2 or lower.

[0044] In the above general formula, the ratio "y" of component O only needs to satisfy the relationship "1.5≤y≤2.1". For example, the ratio "y" of component O can be 1.6 or higher, 1.7 or higher, 1.8 or higher, or 1.9 or higher. For example, the ratio "y" of component O can be 2.0 or lower.

[0045] In the above general formula, the Ni composition ratio "a", the Co composition ratio "b", and the Mn composition ratio "c" satisfy the relationship "a+b+c=1.0".

[0046] In the above general formula, the Ni composition ratio "a" only needs to satisfy the relationship "0.5≤a≤1.0". For example, the Ni composition ratio "a" can be 0.6 or higher, 0.7 or higher, 0.8 or higher, or 0.85 or higher. For example, the Ni composition ratio "a" can be 0.9 or lower.

[0047] In the above general formula, the Co composition ratio "b" only needs to satisfy the relationship "0 ≤ b ≤ 0.3". For example, the Co composition ratio "b" can be 0.01 or higher, 0.02 or higher, 0.03 or higher, 0.04 or higher, 0.05 or higher, 0.06 or higher, 0.07 or higher, or 0.075 or higher. For example, the Co composition ratio "b" can be below 0.25, below 0.20, below 0.15, below 0.10, below 0.09, or below 0.08.

[0048] In the above general formula, the composition ratio "c" of Mn only needs to satisfy the relationship "0 ≤ c ≤ 0.3". For example, the composition ratio "c" of Mn can be 0.01 or higher, 0.02 or higher, 0.03 or higher, 0.04 or higher, 0.05 or higher, 0.06 or higher, 0.07 or higher, or 0.075 or higher. For example, the composition ratio "c" of Mn can be less than 0.25, less than 0.20, less than 0.15, less than 0.10, less than 0.09, or less than 0.08.

[0049] Any dopant can be added to the lithium transition metal composite oxide. The dopant refers to an element other than Li, Ni, Co, Mn, and O. The dopant may, for example, contain at least one element selected from Zr, Mo, Mg, Ca, Na, Fe, Cr, Zn, Si, Sn, Al, and Ag. The dopant composition ratio d relative to a+b+c=1.0 can, for example, be 0.005 or more, 0.01 or more, 0.02 or more, 0.03 or more, or 0.04 or more. The dopant composition ratio d relative to a+b+c=1.0 can, for example, be 0.05 or less.

[0050] The positive electrode active material can have a shape consisting of two or more primary particles stacked together, or it can have a shape consisting of n primary particles stacked together. Here, n can be an integer greater than or equal to 2, and the upper limit can be, for example, less than 100, less than 50, less than 4, or less than 3.

[0051] The primary particles of the positive electrode active material are single crystals with a crystal structure belonging to space group R-3m. A single crystal is defined as a single, independent particle (primary particle) that appears non-aggregated in a SEM image. Single crystals do not appear to have grain boundaries in SEM images. The magnification of SEM images can be, for example, 10,000x to 30,000x.

[0052] The crystal structure of primary particles in positive electrode active materials can be a layered rock salt structure.

[0053] The positive electrode active material can be polycrystalline, consisting of two or more primary particles. The positive electrode active material has one or more grain boundaries in the SEM image, with upper limits such as below 100, below 50, below 10, below 3, or below 2.

[0054] The positive electrode active material can be a particle. The positive electrode active material particle can be a secondary particle formed by stacking two or more primary particles.

[0055] The particle size of primary particles in the positive electrode active material can be 0.5 μm or larger, 0.6 μm or larger, 0.8 μm or larger, or 1.0 μm or larger. If the particle size of the primary particles is too small, the particles will not grow sufficiently, and it may be difficult to fabricate a single crystal. On the other hand, the particle size of the primary particles can be, for example, less than 10 μm, less than 5 μm, or less than 3 μm. The particle size of the primary particles can be determined, for example, by using the longest diameter in TEM or SEM images. In addition, if the positive electrode layer contains primary particles, the particle size of the primary particles can be determined by using the longest diameter of the primary particles in the SEM cross-sectional image of the positive electrode layer. The "particle size of the primary particles" mentioned here is not the average particle size. That is, when the positive electrode active material contains multiple primary particles, the "particle size of the primary particles" refers to the "particle size of each individual primary particle".

[0056] The average particle size of the positive electrode active material can be, for example, greater than 0.5 μm or greater than 1.0 μm. The average particle size of the positive electrode active material can be less than 100 μm or less than 30 μm.

[0057] The primary particles constituting the positive electrode active material are stacked in an orientation in which the 003 planes of each primary particle are parallel.

[0058] In this disclosure, parallelism includes not only perfect parallelism, but also a slightly inclined configuration within a range of ±5 degrees.

[0059] The primary particles constituting the positive electrode active material can be made to not stack in the direction parallel to the 003 plane. By preventing the primary particles from stacking in the direction parallel to the 003 plane, the diffusion distance of lithium ions within the positive electrode active material in the direction parallel to the 003 plane can be shortened.

[0060] The positive electrode active material, formed by stacking two or more primary particles with their 003 planes parallel, can have a long axis and a short axis, with the short side of the positive electrode active material parallel to the 003 plane. By aligning the short side of the positive electrode active material with the 003 plane, compared to aligning the long side of the positive electrode active material with the 003 plane, the diffusion distance of lithium ions within the positive electrode active material can be shortened.

[0061] In a direction parallel to the 003 plane of each primary particle, the ratio of the length of the shortest primary particle to the length of the longest primary particle is 0.95 to 1. This is an indicator of the degree of stacking shift of the primary particles contained in the positive electrode active material, as long as the stacking shift of the primary particles is within the range of 0% to 5%.

[0062] When cross-sectioning the positive electrode active material using a transmission electron microscope, the lengths of each primary particle can be equal in the direction parallel to the 003 plane of each primary particle. The length of a primary particle can be its diameter or not. When the length of a primary particle is the longest diameter of the primary particle in the TEM or SEM image, it is considered the diameter of the primary particle. Since adjacent primary particles have equal lengths in the direction parallel to the 003 plane of each primary particle, the outer edge observed when cross-sectioning the positive electrode active material can expose the 003 plane originating from the primary particles in the direction parallel to the 003 plane of each primary particle, and other surfaces besides the 003 plane of each primary particle can be exposed on the surface in the direction perpendicular to the 003 plane of each primary particle.

[0063] Other than the 003 facet of each primary particle, the other faces can be the 012 facet, the 101 facet, the 104 facet, or the 110 facet.

[0064] Among them, when the positive electrode active material is cross-sectioned using a transmission electron microscope, the outer edge of the positive electrode active material can expose the 003 surfaces of the primary particles at both ends of the stacking direction in a direction parallel to the 003 surfaces of each primary particle, and expose the 104 surfaces of each primary particle on a surface in a direction perpendicular to the 003 surfaces of each primary particle.

[0065] 2. Method for manufacturing positive electrode active material

[0066] This disclosure provides a method for manufacturing the above-mentioned positive electrode active material, comprising: a first-stage calcination step, wherein a first mixture of a transition metal hydroxide and a lithium compound is calcined at 700°C to 1100°C to obtain a precursor of the positive electrode active material; a magnetic field application step, wherein a magnetic field is applied to a slurry formed by dispersing the precursor of the positive electrode active material in a solvent; a drying step, wherein the slurry is dried to obtain a dried product; a second-stage calcination step, wherein the dried product is calcined at 800°C to 1000°C to obtain a second-stage calcined product; and a cooling step, wherein the second-stage calcined product is cooled at a cooling rate of 0.2°C / min to 0.5°C / min to obtain the positive electrode active material.

[0067] The method for manufacturing the positive electrode active material disclosed herein includes (1) a first-stage firing process, (2) a magnetic field application process, (3) a drying process, (4) a second-stage firing process, and (5) a cooling process.

[0068] In this disclosure, primary particles of a transition metal hydroxide are synthesized. These particles are then subjected to a first-stage calcination to obtain a precursor of the positive electrode active material. Next, a magnetic field is applied to a slurry containing the precursor to magnetically orient the precursor, thereby aligning the crystal orientation of the primary particles within the precursor. The slurry is then dried, and a second-stage calcination allows the 003 faces of the primary particles to connect with each other. Finally, cooling at a predetermined rate reduces the stacking misalignment of the primary particles.

[0069] (1) First stage firing process

[0070] The first stage firing process involves firing a first mixture of transition metal hydroxide and lithium compound at 700°C to 1100°C to obtain the precursor of the above-mentioned positive electrode active material.

[0071] The method for manufacturing transition metal hydroxides disclosed herein is not particularly limited, and examples include the following methods. First, an aqueous solution of the transition metal hydroxide as a raw material is prepared. For example, a method for preparing the aqueous solution can be described by dissolving a water-soluble transition metal compound in water. Examples of transition metal compounds include metal salts such as sulfates and nitrates. Examples of Ni sources include NiSO4 and Ni(NO3)2. Examples of Co sources include CoSO4, Co(NO3)2, and Co(NO3)3. Examples of Mn sources include MnSO4 and Mn(NO3)2. The composition of the aqueous solution can be appropriately adjusted according to the target positive electrode active material.

[0072] Next, a certain amount of NH3 aqueous solution is added to the reaction vessel, and nitrogen replacement is carried out while stirring with a stirrer to form a non-oxidizing atmosphere. The nitrogen flow rate for nitrogen replacement is not particularly limited, for example, it can be set to 2~6 L / min.

[0073] Next, an aqueous solution of sodium hydroxide is added to the reaction vessel, while maintaining the pH at an alkaline level (e.g., pH 11.3–12.0). Over one hour, the above-mentioned aqueous solutions of raw materials and NH3 are added dropwise to the reaction vessel. The reaction temperature is not particularly limited; for example, it can be set above 50°C and below 65°C.

[0074] After the reaction is complete, pre-firing can be carried out. Pre-firing can be carried out, for example, at 120℃~220℃, 4~10 hours, and 0.2~1.0 MPa.

[0075] After the reaction or pre-calcination is complete, the washed material is filtered, the transition metal hydroxide is removed, and then dried. The drying process can be carried out, for example, at 110°C for 10 to 12 hours.

[0076] In this disclosure, the transition metal hydroxide contains a transition metal. The transition metal hydroxide may be a nickel-cobalt-manganese complex hydroxide comprising nickel (Ni), cobalt (Co), and manganese (Mn). In the nickel-cobalt-manganese complex hydroxide, the molar ratio of each metal relative to the total stoichiometry of nickel, cobalt, and manganese is the same as the compositional ratio shown in the above general formula for lithium transition metal complex oxides in the positive electrode active material.

[0077] Examples of lithium compounds (Li sources) include at least one selected from lithium carbonate, lithium nitrate, lithium acetate, lithium hydroxide, lithium oxide, and lithium chloride. The lithium compound may be lithium hydroxide. The molar ratio of Li in the Li source to the TM contained in the transition metal hydroxide may be, for example, 0.4 or more, 0.6 or more, 0.8 or more, 1.0 or more, or 1.1 or more, and may be 1.4 or less or 1.2 or less.

[0078] The ratio of lithium compound to transition metal hydroxide in the first mixture is set such that the molar ratio (of lithium and other metals relative to the total stoichiometric ratio (of lithium in the target cathode active material to the total stoichiometric ratio (of metals contained in the transition metal hydroxide)) is typically equal to the molar ratio (of lithium and other metals) in the first mixture. The mixing method is not particularly limited and well-known methods can be used.

[0079] The first mixture may contain a molten salt. By functioning as a flux, the molten salt enables sufficient grain growth of the primary particles. The molten salt may contain Li. Examples of molten salts include lithium hydroxide. The molar ratio (Li / TM) of Li in the molten salt relative to the amount of transition metal hydroxide (TM) in the transition metal hydroxide is, for example, 0.01 or more, 0.05 or more, 0.10 or more, or 0.15 or more. On the other hand, the Li / TM ratio is, for example, 0.60 or less, 0.50 or less, 0.40 or less, or 0.30 or less.

[0080] The first mixture may contain lithium hydroxide as a Li source and a molten salt. The molar ratio of Li in the Li source and the molten salt to the amount of TM in the transition metal hydroxide (Li' / TM) is, for example, 1.01 or more, 1.05 or more, 1.10 or more, or 1.15 or more. On the other hand, the Li' / TM ratio is, for example, 1.60 or less, 1.50 or less, 1.40 or less, or 1.30 or less.

[0081] The first mixture can be used to obtain a lithium transition metal composite oxide, for example, by firing at 700°C to 1100°C for 8 to 15 hours. Firing can be performed using a known firing furnace such as a muffle furnace.

[0082] The lower limit of the firing temperature in the first stage firing process can be above 800℃, above 850℃, above 900℃, or above 950℃, and the upper limit can be below 1000℃.

[0083] The firing time in the first stage of the firing process can be more than 9 hours or more than 10 hours.

[0084] The firing time in the first stage of the firing process can be less than 13 hours or less than 11 hours.

[0085] The precursor of the positive electrode active material obtained by calcining the transition metal hydroxide of this disclosure is usually a single-crystal active material composed of primary particles.

[0086] (2) Magnetic field application process

[0087] The magnetic field application step is a process of applying a magnetic field to a slurry formed by dispersing the precursor of the above-mentioned positive electrode active material in a solvent. The solvent can be N-methylpyrrolidone (NMP), etc. The strength of the applied magnetic field can be 0.8~2T or 1~1.5T. The duration of magnetic field application can be 1 minute to 1 hour or 5 minutes to 10 minutes.

[0088] (3) Drying process

[0089] The drying process is the process of drying the above-mentioned slurry to obtain a dried product. The drying temperature can be, for example, 90°C to 110°C, or 100°C. The drying time can be, for example, 1 minute to 1 hour, or 5 minutes to 10 minutes.

[0090] (4) Two-stage firing process

[0091] The second-stage firing process involves firing the aforementioned dried material at 800°C to 1000°C to obtain the second-stage fired product. The lower limit of the firing temperature in the second-stage firing process can be 850°C or higher, or 900°C or higher, and the upper limit can be 950°C or lower. The firing time in the second-stage firing process can be 1 hour or more, 9 hours or more, or 10 hours or more. Alternatively, the firing time in the second-stage firing process can be 15 hours or less, 13 hours or less, or 11 hours or less.

[0092] (5) Cooling process

[0093] The cooling process involves cooling the second-stage calcined material at a cooling rate of 0.2℃ / min to 0.5℃ / min to obtain the positive electrode active material. A cooling rate of 0.2℃ / min to 0.5℃ / min is sufficient.

[0094] 3. Battery

[0095] The positive electrode active material provided by this disclosure can be used, for example, as the positive electrode active material constituting the positive electrode layer of a battery (such as a lithium-ion battery). That is, this disclosure provides a battery in which a positive electrode layer, an electrolyte layer, and a negative electrode layer are sequentially stacked, and the positive electrode layer contains the positive electrode active material of this disclosure. According to this disclosure, by using the aforementioned positive electrode active material in a battery, the battery resistance can be reduced.

[0096] The type of battery disclosed herein is not particularly limited, but lithium-ion batteries are typical. Furthermore, the battery in this disclosure can be a liquid battery with an electrolyte layer containing an electrolyte solution, or a solid battery with an electrolyte layer containing a solid electrolyte. Solid batteries can be semi-solid batteries or all-solid batteries. In this disclosure, a semi-solid battery is a battery whose electrolyte layer contains both solid components such as inorganic solid electrolytes and liquid components (e.g., solvents and electrolyte solutions). In this disclosure, an all-solid battery is a battery whose electrolyte layer contains only solid components such as inorganic solid electrolytes as the electrolyte. Additionally, the battery in this disclosure can be a primary battery or a secondary battery, wherein it can be a secondary battery. This is because it can be repeatedly charged and discharged, making it useful, for example, as a vehicle battery.

[0097] There are no particular limitations on the shape of the battery; for example, it can be coin-shaped, cylindrical, square, sheet-shaped, button-shaped, flat, or stacked.

[0098] In the case of a battery pack with multiple batteries stacked together, the battery pack can be either unipolar or bipolar.

[0099] Batteries are used in various applications, including as power sources for vehicles such as hybrid electric vehicles (HEVs), plug-in hybrid electric vehicles (PHEVs), battery electric vehicles (BEVs), gasoline vehicles, and diesel vehicles. In particular, they can be used as power sources for driving hybrid electric vehicles (HEVs), plug-in hybrid electric vehicles (PHEVs), or battery electric vehicles (BEVs). Furthermore, batteries can be used as power sources for mobile bodies other than vehicles (e.g., railways, ships, aircraft) and for electrical products such as information processing devices.

[0100] Furthermore, this disclosure is not limited to the embodiments described above. The embodiments described above are illustrative, and may have a structure that is substantially the same as the technical concept described in the claims of this disclosure and achieves the same effect. Any structure is included within the technical scope of this disclosure.

[0101] Example 1

[0102] Synthesis of transition metal hydroxides

[0103] NiSO4, CoSO4, and MnSO4 were dissolved in ion-exchanged water to prepare a raw material aqueous solution. The molar ratio of Ni, Co, and Mn in the raw material aqueous solution was Ni:Co:Mn = 80:10:10. The concentration of the raw material aqueous solution (the proportion of all raw materials to the raw material aqueous solution) was 30% by mass.

[0104] Hydrothermal synthesis (crystallization)

[0105] A certain amount of NH3 aqueous solution was added to the reaction vessel, and the mixture was stirred while nitrogen was purged from the gas. NaOH aqueous solution was then added to the reaction vessel to maintain an alkaline pH (pH=12). While maintaining a controlled temperature, the above-mentioned raw material aqueous solution and NH3 aqueous solution were added dropwise to precipitate the transition metal hydroxide. The reaction temperature was 60℃, and the reaction time was 10 hours.

[0106] filter

[0107] After hydrothermal synthesis, the transition metal hydroxide is dispersed using ion-exchanged water and then washed with water. The washed transition metal hydroxide is then filtered and removed.

[0108] dry

[0109] The transition metal hydroxide was dried at 120°C for 16 hours to evaporate the moisture.

[0110] Synthesis of positive electrode active material

[0111] Li raw material mixing

[0112] Dry transition metal hydroxide and LiOH, a lithium compound serving as the Li source, were mixed in an agate mortar to obtain a mixture. The mixture was prepared such that the molar ratio of the lithium compound to the total NCM (Ni, Co, and Mn) contained in the transition metal hydroxide (Li / NCM ratio) was 1.1.

[0113] First stage of firing

[0114] The resulting mixture was calcined in a furnace at 1000°C under an oxygen atmosphere for 10 hours to synthesize the positive electrode active material (Li). 1.1 Ni 0.8 Co 0.1 Mn 0.1 O2),

[0115] The first stage of firing is obtained.

[0116] Phase One Break

[0117] The first-stage fired material is crushed using a jet mill, which acts as a pulverizer, to a specified particle size.

[0118] Magnetic field orientation

[0119] Add 100ml of NMP and 50g of the first-stage firing material to a beaker, stir, and obtain a slurry. Let the slurry stand for 10 minutes in a space with 1T magnets positioned above and below.

[0120] Slurry drying

[0121] After settling, gently move the beaker into the dryer and dry the slurry at 150°C for 6 hours.

[0122] Second stage of firing

[0123] The dried material was gently transferred to an alumina crucible and calcined in a furnace at 800°C in an oxygen atmosphere for 10 hours to obtain the second-stage calcined product of the positive electrode active material.

[0124] cool down

[0125] The resulting second-stage fired product was cooled in an oxygen atmosphere at a cooling rate of 0.2 °C / min.

[0126] Second stage of fragmentation

[0127] The second-stage calcined material is pulverized using a grinding mill, and the positive electrode active material, which is the second-stage calcined material, is pulverized to a specified particle size to obtain particles of the positive electrode active material.

[0128] Example 2

[0129] In the above-mentioned "cooling" process, the cooling rate was set to 0.5°C / min. Otherwise, the positive electrode active material was prepared in the same manner as in Example 1.

[0130] Comparative Example 1

[0131] In the above-mentioned [synthesis of positive electrode active material], the process from <magnetic field orientation> to <second stage crushing> is not performed. The particles of the first stage calcined product obtained in the <first stage crushing> of [synthesis of positive electrode active material] are used as positive electrode active material. Otherwise, the positive electrode active material is prepared in the same manner as in Example 1.

[0132] Comparative Example 2

[0133] In the above-mentioned "cooling" process, the cooling rate was set to 2.0°C / min. Otherwise, the positive electrode active material was prepared in the same manner as in Example 1.

[0134] TEM analysis

[0135] The positive electrode active materials of Examples 1-2 and Comparative Examples 1-2 were observed using TEM images.

[0136] For the positive electrode active materials of Examples 1 and 2, it was observed that at the outer edge observed using TEM cross-sectional images, the 003 surfaces of the primary particles at both ends of the stacking direction were exposed, and on the surface of each primary particle in the direction perpendicular to the 003 surface, the 104 surfaces of each primary particle were exposed.

[0137] In the cross-sectional view of the positive electrode active material using TEM, it was confirmed that the positive electrode active materials of Examples 1 and 2 were stacked in an orientation parallel to the 003 plane of each primary particle.

[0138] In the cross-sectional view of the positive electrode active material using TEM, it was confirmed that in the direction parallel to the 003 plane, the ratio of the length of the shortest primary particle to the length of the longest primary particle among multiple primary particles in the positive electrode active materials of Examples 1 and 2 was in the range of 0.95 to 1 (the stacking offset of the primary particles was less than 5%).

[0139] In the cross-sectional view of the positive electrode active material using TEM, it was confirmed that the primary particles of the positive electrode active materials of Examples 1 and 2 do not stack in the direction parallel to the 003 plane of each primary particle, and the short side direction of the positive electrode active materials of Examples 1 and 2 is parallel to the 003 plane of each primary particle.

[0140] In the cross-sectional view of the positive electrode active material using TEM, it was confirmed that in the direction parallel to the 003 plane, the ratio of the length of the shortest primary particle to the length of the longest primary particle among the multiple primary particles in the positive electrode active materials of Comparative Examples 1 to 2 was less than 0.95 (the stacking offset of the primary particles exceeded 5%).

[0141] Battery (wound cylindrical battery) manufacturing

[0142] Using the positive electrode active materials of Examples 1-2 and Comparative Examples 1-2, wound cylindrical batteries of Examples 1-2 and Comparative Examples 1-2 were prepared.

[0143] Specifically, firstly, using a coating machine (manufactured by Allgood Co., Ltd.) equipped with a film thickness adjustment function, a positive electrode composite slurry containing a positive electrode active material, acetylene black as a conductive material, and polyvinylidene fluoride as a binder is coated onto the surface of a metal foil serving as the positive electrode current collector. Then, it is dried at 80°C for 5 minutes using a dryer to create a positive electrode with a positive electrode layer on the positive electrode current collector. The composition of the positive electrode composite slurry is: positive electrode active material: conductive material: binder = 88:10:2 by mass.

[0144] On the other hand, using a coating machine (manufactured by Allgood Co., Ltd.) equipped with a film thickness adjustment function, a negative electrode composite slurry containing natural graphite as the negative electrode active material, styrene-butadiene rubber (SBR) as a binder, and carboxymethyl cellulose (CMC) as a thickener is coated onto the surface of a metal foil serving as the negative electrode current collector. Then, it is dried at 80°C for 5 minutes using a dryer to produce a negative electrode with a negative electrode layer on the negative electrode current collector.

[0145] Prepare a 1M LiPF6 solution as the electrolyte, containing LiPF6 as the electrolyte and ethylene carbonate (EC), dimethyl carbonate (DMC), and ethyl methyl carbonate (EMC) as solvents in a volume ratio of EC / DMC / EMC = 3 / 3.

[0146] The above-mentioned positive electrode, separator and negative electrode are stacked, and the above-mentioned electrolyte is impregnated in the separator to produce wound cylindrical batteries of Examples 1 to 2 and Comparative Examples 1 to 2.

[0147] Battery reviews

[0148] For each wound cylindrical battery produced, the initial capacity and IV resistance were measured.

[0149] Determination of initial capacity

[0150] Within a voltage range of 3.0 V to 4.3 V, the capacity was measured when charged at a C rate of 0.3 C at a temperature of 50 °C. The results are shown in Table 1. The initial capacities of Examples 1 to 2 and Comparative Examples 1 to 2 shown in Table 1 are relative values ​​when the initial capacity of Comparative Example 1 is set to 100%.

[0151] IV resistance measurement

[0152] Within a voltage range of 3.0 V to 4.3 V, the upper limit voltage of 4.3 V is set to SOC 100%, and the voltage is adjusted to achieve SOC 50%.

[0153] The voltage drop (V) was measured during a 10-second discharge at various C-rates of 0°C, 0.1°C, 0.3°C, 0.5°C, 0.7°C, and 1.0°C. The voltage drop (V) was plotted against the current value, and the slope of the approximate straight line drawn by a linear function was taken as the IV resistance. The results are shown in Table 1. The resistance values ​​of Examples 1-2 and Comparative Examples 1-2 shown in Table 1 are relative values ​​when the resistance value of Comparative Example 1 is set to 100%.

[0154] (Table 1)

[0155]

[0156] As shown in Table 1, it can be seen that the batteries using the positive electrode active materials of Examples 1 and 2 have a larger initial capacity and a smaller IV resistance compared to the batteries using the positive electrode active materials of Comparative Examples 1 and 2. Therefore, it can be concluded that by using a positive electrode active material in which the primary particles are stacked in a manner parallel to the 003 plane of each primary particle in a TEM-based cross-sectional image, and in which the ratio of the length of the shortest primary particle to the length of the longest primary particle is 0.95 to 1 in a direction parallel to the 003 plane of each primary particle, the initial capacity of the battery can be increased and the IV resistance can be reduced.

Claims

1. A positive electrode active material, The positive electrode active material contains at least one element selected from Ni, Co, and Mn. The positive electrode active material has a shape consisting of two or more primary particles stacked together. The primary particle is a single crystal with a crystal structure belonging to space group R-3m. Each of the primary particles is stacked with its 003 face parallel to that of the primary particle. In a direction parallel to the 003 plane of each of the primary particles, the ratio of the length of the shortest primary particle to the length of the longest primary particle is 0.95 to 1.

2. The positive electrode active material according to claim 1, wherein, The positive electrode active material has a shape consisting of two or more but less than ten primary particles stacked together. The primary particles do not stack in a direction parallel to the 003 plane of each primary particle. The short side of the positive electrode active material is parallel to the 003 plane of each primary particle.

3. The positive electrode active material according to claim 1, wherein, When the positive electrode active material is cross-sectionally examined using a transmission electron microscope, the outer edge of the positive electrode active material exposes the 003 surface originating from each of the primary particles in a direction parallel to the 003 surface of each of the primary particles, and exposes other surfaces besides the 003 surface of each of the primary particles in a direction perpendicular to the 003 surface of each of the primary particles. The other faces of each primary particle besides the 003 face are the 012 face, 101 face, 104 face, or 110 face.

4. A battery comprising a positive electrode layer including the positive electrode active material as described in claim 1.

5. The method for manufacturing the positive electrode active material according to claim 1, comprising: In the first stage of the firing process, a first mixture of transition metal hydroxide and lithium compound is fired at 700°C to 1100°C to obtain the precursor of the positive electrode active material. The magnetic field application process involves applying a magnetic field to a slurry formed by dispersing the precursor of the positive electrode active material in a solvent. The drying process dries the slurry to obtain a dried product. The second stage firing process involves firing the dried material at 800℃~1000℃ to obtain the second stage fired material. and In the cooling process, the second-stage fired material is cooled at a rate of 0.2℃ / min to 0.5℃ / min to obtain the positive electrode active material.

Citation Information

Patent Citations

  • Electrode active material, and method of manufacturing the same

    JP2013065397A